Human aggression (Part 3) - Jumat, Rahiman (2012)
This theory sees aggression as social learning. According to social learning theories in earlier studies, people acquire aggressive responses the same way they acquire other complex forms of social behavior which either by direct experience or by observing others. Social learning theory explains the acquisition of aggressive behaviors, via observational learning processes, and provides a useful set of concepts for understanding and describing the beliefs and expectations that guide social behavior